ANALISIS PEMBOROSAN PEMAKAIAN AIR REGENERASI MENGGUNAKAN METODE REGRESI: ANALISIS PEMBOROSAN PEMAKAIAN AIR REGENERASI MENGGUNAKAN METODE REGRESI - Agus Wiranto (Journal of Research and Publication Innovation, 2023)
Agro-industry in Indonesia that has been developing for a long time, one example is the sugar industry. Sugar is a food and beverage additive which is a source of energy and the main trading commodity in Indonesia. Glucose syrup can be produced from the transformation of raw materials such as cassava. In Indonesia cassava plants are very abundant so that until now there have been many industries that produce glucose syrup. PT TGLC glucose industry is a company engaged in the glucose syrup industry. This research activity is more emphasized on the production process and production management system (waste loss that occurs). In the liquid sugar production process a regeneration process is the process of recovering the resin used in the ion exchanger column. The object of our research is to use water sparingly, the waste or loss that occurs can reduce the problem of wasteful use of water in the regeneration process, because it is Achievable. RW and RRO of 2.35 at the moment. Previously, there was no research on the use of water in the production process. The method that will be used is analysis of aspects of the process and management of glucose production from how to prepare raw materials, how the stages are passed to be able to carry out the planned process and how to control things that are not suitable in production management so as to increase the profit of glucose production in This Food Company. The advantages of research using a decision support system or DSS (Decision Support System) method is that in this study it is a Simple Linear Regression Statistical Method which functions to test how the causal relationship between the Causal Factor Variable (X) and the Consequent Variable in carrying out research methods is used There are several methods to obtain the right data and analysis. As for the lack of a decision support system or DSS (Decision Support System) method, we will complement it using several methods by direct field observation of the glucose product production process and management system. This observation includes interactive activities in the form of interviews, discussions and introduction of employees who work at the company . Interaction is carried out as a supporting activity in an effort to clarify and analyze problems The purpose of this research is to apply the decision support system method or DSS (Decision Support System) which is a Simple Linear Regression, namely a statistical method that functions to test how the causal relationship between the Causative Factor Variable (X) and the Variable As a result, several methods are used in carrying out research activities. to get the right data and analysis. So that it can help work in the field carried out to experience directly the process of saving, work on the aspect being studied, and literature study is carried out by looking for references and literature related to the activities carried out, both from literature studies and data and information obtained from industry. The achievement target to be achieved in this study is to reduce the use of regenerated water in RW and RRO water from 2.35 m3/ton glucose to 0.74 m3/ton glucose by utilizing condensate & forward water - ion exchangers.